Uncarboxylated osteocalcin induced miR-143-3p targets SP7 and activates PI3K/Akt signaling in TNBC cells to promote invasion and migration - Qian Du; Jiaojiao Xu; Miao Zhang; Jianhong Yang (Translational Oncology)
Triple-negative breast cancer (TNBC) is an exceptionally aggressive malignancy with poor prognosis. Patients often have elevated mortality and recurrence rates, along with a pronounced risk of distant metastasis. Our earlier research highlighted the role of uncarboxylated osteocalcin (GluOC) in fueling TNBC cell proliferation and metastasis; however the molecular underpinnings of its impact on cancer invasion and migration remain enigmatic. In this study, we identified miR-143-3p as a significantly downregulated miRNA following GluOC treatment in TNBC cells. Notably, increased miR-143-3p has been linked to more favorable clinical outcomes in patients with TNBC. miR-143-3p expression has been shown to target and repress the expression of SP7. Furthermore, our findings indicate that GluOC modulates the miR-143-3p/PI3K/Akt signaling pathway, which in turn fosters the invasive and migratory capabilities of TNBC cells. In a xenograft animal model, we observed that the administration of GluOC led to a marked enhancement in tumor growth. Conversely, the delivery of miR-143-3p agomir was associated with a notable reduction in tumor growth. Notably, concurrent administration of miR-143-3p agomir and GluOC partially abrogated the tumorigenic effects induced by GluOC alone. Furthermore, GluOC downregulated the expression of miR-143-3p. Our study findings indicate that GluOC plays a role in the invasion and migration of TNBC cells by regulating the miR-143-3p/SP7 and miR-143-3p/PI3K/Akt axes. These insights suggest that GluOC and miR-143-3p are integral to the invasive and migratory processes of TNBC cells and may serve as promising targets for therapeutic interventions in TNBC.